Measurement of the azimuthal anisotropy of charged-particle production in Xe plus Xe collisions at √SNN=5.44 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; et al. (Physical review, 2020)
This paper describes the measurements of flow harmonics v(2)-v(6) in 3 mu b(-1) of Xe Xe collisions at root S-NN = 5.44 TeV performed using the ATLAS detector at the Large Hadron Collider (LHC). Measurements of the centrality, multiplicity, and p(T) dependence of the v(n) obtained using two-particle correlations and the scalar product technique are presented. The measurements are also performed using a template-fit procedure, which was developed to remove nonflow correlations in small collision systems. This nonflow removal is shown to have a significant influence on the measured v(n) at high p(T), especially in peripheral events. Comparisons of the measured v(n) with measurements in Pb + Pb collisions and p + Pb collisions at root S-NN = 5.02 TeV are also presented. The v(n) values in Xe + Xe collisions are observed to be larger than those in Pb + Pb collisions for n = 2, 3, and 4 in the most central events. However, with decreasing centrality or increasing harmonic order n, the v(n) values in Xe + Xe collisions become smaller than those in Pb + Pb collisions. The v(n) in Xe + Xe and Pb + Pb collisions are also compared as a function of the mean number of participating nucleons, < N-part >, and the measured charged-particle multiplicity in the detector. The v(3) values in Xe + Xe and Pb + Pb collisions are observed to be similar at the same < N-part > or multiplicity, but the other harmonics are significantly different. The ratios of the measured v(n) in Xe + Xe and Pb + Pb collisions, as a function of centrality, are also compared to theoretical calculations.
ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, L. Henkelmann, J. Jongmanns, M. Klassen, A. Krishnan, A. Kugel, K. Mkrtchyan, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schöning, H.-C. Schultz--Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, S.M. Weber, M. Wessels, X. Yue und 2864 weitere
SNN steht unterhalb des Wurzelzeichens
Gesehen am 07.04.2020